Faktor Yang Memengaruhi Kejadian Tuberkulosis Paru Pada Balita Stunting Di Wilayah Kerja Puskesmas Baki Kabupaten Sukoharjo - Septian Sekar Ary Rahmawati; Angnes, Sunardi Yeni L; Mirasa, Yudied Agung (State Islamic University of Sunan Ampel, 2025)
Stunted children are more vulnerable to tuberculosis (TB) compared to those with normal nutritional status. Pediatric TB remains a critical component in the overall TB control efforts in Indonesia. This study aims to analyze the factors influencing the incidence of pulmonary TB among stunted children in Baki Subdistrict, Sukoharjo Regency. This was an observational analytic study with a cross-sectional approach, conducted at the Baki Community Health Center in June 2025. A total of 94 stunted children were selected from a population of 122 using total sampling. Independent variables included child’s age, gender, parental education and income, access to healthcare services, and BCG vaccination status. The dependent variable was the incidence of pulmonary TB. Data were collected using questionnaires and analyzed using Chi-square tests and logistic regression. The prevalence of pulmonary TB among stunted children was 32.5%. No significant association was found between age or gender and TB incidence. However, maternal education, household income, access to healthcare services, and BCG vaccination status were significantly associated with TB incidence. Children without complete BCG immunization were at higher risk of TB (OR ≈ 2.75; p = 0.017). BCG vaccination status is the most dominant factor associated with pulmonary TB incidence among stunted children. It is recommended to improve the coverage and quality of basic immunization services, implement active TB screening in stunted children, expand access to healthcare services, and integrate stunting prevention with pediatric TB control programs.